Factors that Motivate The Act of Earnings Management - Janet Jesslyn; Yulius Kurnia Susanto; Williem Chahya Wijaya (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
The purpose of this research is to obtain empirical evidence about the influence of return on asset, financial leverage, firm size, firm age, fixed asset turnover, free cash flow, sales growth, audit quality, managerial ownership, institutional ownership, board size, and audit committee on earnings management. The population used in this research are non financial companies listed in Indonesia Stock Exchange from 2017 to 2019. The sample used for this research consists of 195 listed non-financial companies. The sampling technique used purposive sampling method, tested and analyzed using multiple regression method. The result of this research shows that return on asset, financial leverage, sales growth, and audit committee has positive influence while fixed asset turnover and free cash flow has negative influence on earnings management, moreover the other independent variables such as firm size, firm age, audit quality, managerial ownership, institutional ownership, and board size have no influence on earnings management.